2022
DOI: 10.1590/s2175-97902022e21266
|View full text |Cite
|
Sign up to set email alerts
|

A study on diabetes-related self-care plan and its determinants among diabetes patients in a Warangal region, Telangana, India

Abstract: The prevalence of epidemiological diseases, including diabetes, has continued to increase because of the adaption of Western culture and the lack of self-care activities among patients with diabetes. Therefore, in this cross-sectional study, we aimed to assess self-care plans and determinants among diabetes outpatients in Warangal. We conducted a prospective observational study among diabetes outpatient clinic in Warangal, India over 6 months from October 2019 to March 2020. We used the expanded Summary of Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…[32] For the purpose of managing of obesity, physical activity and following adequate dietary habits are proven methods to control obesity and associated risks. [33][34][35][36][37][38][39] Ephedra is an herb that was historically utilized to aid in weight loss. The Food and Drug Administration has officially banned it due to serious consequences such as mood swings, high blood pressure, irregular heart rhythm, strokes, seizures, and heart attacks.…”
Section: Discussionmentioning
confidence: 99%
“…[32] For the purpose of managing of obesity, physical activity and following adequate dietary habits are proven methods to control obesity and associated risks. [33][34][35][36][37][38][39] Ephedra is an herb that was historically utilized to aid in weight loss. The Food and Drug Administration has officially banned it due to serious consequences such as mood swings, high blood pressure, irregular heart rhythm, strokes, seizures, and heart attacks.…”
Section: Discussionmentioning
confidence: 99%
“…[32] For the purpose of managing of obesity, physical activity and following adequate dietary habits are proven methods to control obesity and associated risks. [33][34][35][36][37][38][39] Ephedra is an herb that was historically utilized to aid in weight loss. The Food and Drug Administration has officially banned it due to serious consequences such as mood swings, high blood pressure, irregular heart rhythm, strokes, seizures, and heart attacks.…”
Section: Discussionmentioning
confidence: 99%
“…During the period of study, we found approximately 600 undergraduates from both colleges at the KSU campus were taking their courses. Similar to previous studies we computed the sample size [21][22][23][24] using an online sample size calculator with a 95% confidence level and a predetermined margin of error of 5%, as in prior investigations. Because we were unclear of the potential outcomes for each question, we assumed that the response distribution for each question would equal 50%.…”
Section: Study Questionnaire Data Collection and Sourcementioning
confidence: 99%